2018
DOI: 10.18632/oncotarget.24617
|View full text |Cite
|
Sign up to set email alerts
|

Consensus molecular subtypes classification of colorectal cancer as a predictive factor for chemotherapeutic efficacy against metastatic colorectal cancer

Abstract: The consensus molecular subtypes (CMS) classification is one of the most robust colorectal cancer (CRC) classifications based on comprehensive gene expression profiles. This study aimed to clarify whether the CMS is a predictive factor for therapeutic effects of standard chemotherapies for metastatic CRC (mCRC). We retrospectively enrolled 193 patients with mCRCs, and using comprehensive gene expression data, classified them into 4 subtypes: CMS1–CMS4. The associations between the subtypes and treatment outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
118
1
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(141 citation statements)
references
References 45 publications
5
118
1
6
Order By: Relevance
“…This is in line not only with the prognostic relevance of CMS reported before [5] but also with data from the adjuvant PETACC8 study as well as the palliative CALGB80405 study, both presented at ASCO annual meeting in 2017 [11,13]. While FIRE-3 is the only study with FOLFIRI as the predefined chemotherapeutic backbone, there seems to be no significant [14] difference in the prognostic effect of CMS with regard to FOLFOX or FOLFIRI treatment [14]. This raises the question whether the CMS classification may be used to predict efficacy of either the EGFR antibody cetuximab or the VEGF-A antibody bevacizumab, both in combination with FOLFIRI.…”
Section: Discussionsupporting
confidence: 77%
“…This is in line not only with the prognostic relevance of CMS reported before [5] but also with data from the adjuvant PETACC8 study as well as the palliative CALGB80405 study, both presented at ASCO annual meeting in 2017 [11,13]. While FIRE-3 is the only study with FOLFIRI as the predefined chemotherapeutic backbone, there seems to be no significant [14] difference in the prognostic effect of CMS with regard to FOLFOX or FOLFIRI treatment [14]. This raises the question whether the CMS classification may be used to predict efficacy of either the EGFR antibody cetuximab or the VEGF-A antibody bevacizumab, both in combination with FOLFIRI.…”
Section: Discussionsupporting
confidence: 77%
“…We have developed and validated a CTX-S signature score, using outcomes data from two independent, prospective clinical trials, as well as by an in vitro cetuximab-treated cell line dataset. The robustness of the CTX-S score is also supported by the findings that: (i) the score was not prognostic; (ii) the score had a strong correlation with EREG and AREG, the predictive biomarkers of cetuximab response (4,6,36,37); (iii) the score was significantly associated with the CMS2 subtypes, which were recently reported to be associated with better cetuximab response (38,39).…”
Section: Discussionmentioning
confidence: 73%
“…To date, reliable molecular markers for the FOLFOX/CapeOX regimen resistance in CRC patients are still unavailable, especially for the primary resistance Moreover, we analyzed the data in the GEO dataset, and found eight datasets, GSE19860, GSE52735, GSE104645, GSE14095, GSE83889, GSE72968, GSE110785, and GSE69657 were contained CRC patients who received FOLFOX chemotherapy (Watanabe et al, 2011;Li et al, 2013;Estevez-Garcia et al, 2015;Tong et al, 2015;Del et al, 2017;Cherradi et al, 2017;Kwon et al, 2017;Okita et al, 2018;Cherradi et al, 2019). We further analyzed the above datasets, the results demonstrated that the datasets, GSE104645, GSE110785, GSE19860, GSE52735, and GSE14095, including the information about acquired resistance and lacked the primary resistance.…”
Section: Discussionmentioning
confidence: 99%